The Composition Process of FLS3N Dance Music 'Ratapan Bumi' Through the Digital Audio Workstation Studio One 6 Approach: A Study of Creation Methodology - Martiano, Vereki; Zaidi, Ahmad; Pardi, Ari; Surayya, Yade; Alhamda Putra, Vindo (Institut Seni Indonesia Padangpanjang, 2025)
This study aims to holistically analyze and describe the creation methodology utilized by composer Vic Art. in producing the accompanying music for the FLS3N (National Student Art and Literature Competition Festival) dance, Ratapan Bumi (The Earth's Lament). This dance work possesses high narrative complexity, addressing the environmental crisis issue in Riau and integrating the Riau Malay philosophy (